Phase behaviour study on medium-chain triglyceride/surfactant/water systems containing gemcitabine using phase inversion composition technique - Wahgiman, Nadiatul Atiqah; Salim, Norazlinaliza; Abdul Rahman, Mohd Basyaruddin (Malaysian Analytical Sciences Society, 2020)
In this study, the phase behavior of medium-chain triglyceride (MCT)/surfactant/water containing gemcitabine (GEM) was investigated. Ternary phase diagrams (TPD) were constructed with different surfactants (Span 20, Span 60, Span 80, Tween 80) and a mixture of surfactant (Tween 80:Span 80, at ratio 1:1). Two observations were recorded, isotropic and multilayer regions. The isotropic region was classified as a transparent, translucent or homogeneous mixture, while the multilayer region was classified as an opaque, milky or heterogeneous mixture. From the ternary phase diagrams constructed, it showed that MCT/(Tween 80: Span 80, ratio 1:1)/ GEM in deionized water system gave the largest isotropic region with the minimum usage of mixed surfactant, where 25% area of the isotropic region was formed with 1% of the usage of surfactant. The composition of F1 (selection based on the ternary phase diagram) was 0.02 % w/w of GEM, 19.98 % w/w of deionized water, 5.00 % w/w of Tween 80:Span 80 at ratio 1:1 and 75 % w/w of MCT. Nanoemulsion formulation was prepared by low energy emulsification method (i.e. phase inversion composition (PIC) technique). As the formulation was prepared in large scale with PIC technique, sodium chloride solution (0.1 M NaCl solution) was added to form a stable formulation as stabilizer. Effect of different volume of NaCl solution (0.5, 1.0 and 1.5 mL) added into formulation was investigated. The results showed that the particle size increased as the amount of NaCl increased, the effect of the amount of NaCl solution is significant towards particles size on F1. The F1 was stable in normal storage condition as it remained a homogeneous formulation against centrifugation test and it was also stable in storage stability test at different temperature (4, 25 and 45 °C) within three months.